Moxibustion for diarrhea in children: A protocol for systematic review and meta-analysis. Issue 17 (30th April 2021) - Li, Peiling; Chi, Zhenhai; You, Jianyu; Deng, Gen; Zhou, Xingchen; Mao, Qiangjian; Pan, Zefeng
Abstract: Background: Infantile Diarrhea is a common and frequent digestive tract disease in children. The causes of this disease are relatively complex and the onset time is relatively long. At present, there is no specific treatment method in Western medicine. Moxibustion is a simple and painless external treatment. However, due to the lack of high-quality evidence to support the effectiveness and safety of moxibustion therapy for pediatric diarrhea. Therefore, the purpose of this study is to verify the effectiveness and safety of moxibustion in the treatment of pediatric diarrhea. Methods: We will use PubMed, Cochrane Library, Wan Fang Database, Web of Science, China National Knowledge Infrastructure Database, Chinese Science Journal Database, China Biomedical Literature Database to carry out a progressive search of diseases. The study will be screened according to eligibility criteria, and quality of the study will be assessed by using the Cochrane Risk of Bias Tool. Results: Through this study, we will systematically evaluate the effectiveness and safety of moxibustion in the treatment of pediatric diarrhea. Conclusion: The results of this study will provide reliable evidence of the safety and effectiveness of moxibustion in the treatment of infantile diarrhea, and provide a therapeutic basis for the future clinical application. Ethics and dissemination: Since this paper does not involve ethical issues, it does not need to pass the review of the ethics committee. It can only collect relevant literature and study. INPLASY Registration number: INPLASY202130091